Defect/Edge‐Selective Functionalization of Carbon Materials by "Direct" Friedel–Crafts Acylation Reaction. Issue 19 (21st February 2017) - Seo, Jeong‐Min; Tan, Loon‐Seng; Baek, Jong‐Beom
Abstract : Popularly utilized oxidation media, via nitric acid/sulfuric acid mixtures, are too corrosive and oxidizing to preserve structural integrity of highly ordered graphitic materials (carbon nanotubes (CNTs) and graphene). Here, for the most commonly used oxidation method, the important advantages of defect/edge‐selective functionalization of carbon materials (CNTs/graphene/graphite) in a polyphosphoric acid (PPA)/phosphorous pentoxide (P2 O5 ) medium are elucidated. The optimized PPA/P2 O5 medium is a mild acid that is not only less corrosive than popularly utilized oxidation media, but also has a strong capability to drive Friedel–Crafts acylation by covalently modifying carbon materials. With a broader spectrum of functional groups accessible, the PPA/P2 O5 ‐driven Friedel–Crafts acylation offers more options for tailoring the properties and processing of carbon materials. Abstract : Defect/edge‐selective Friedel–Crafts acylation in mild polyphosphoric acid/phosphorous pentoxide medium is one of the best alternative methods for scalable, yet simple and efficient, functionalization of carbon materials, which offers more options for tailoring properties and processing of such materials. The method is an alternative to the most commonly utilized oxidation medium, nitric acid/sulfuric acid mixtures, which are too corrosive and causes serious damage to highly ordered graphitic frameworks.